Diglossic Principles in Shona Lexicography - Mangoya, Esau (Lexikos, 2007)
Abstract: This article looks at diglossia in Shona dictionaries. Diglossia is seen here as the differential and preferential use of a language or a dialect in dictionaries. The main language spoken in Zimbabwe is Shona. Over a period of about one and a half century, at least twenty Shona lexicographic publications including glossed word lists and medium-sized dictionaries have appeared, examples of which are used in this article to demonstrate the diglossic principles in Shona lexicography. As is the case with many languages, Shona is also in contact with other languages, among them English, which during the colonial era was declared the official language of the country. As a result the dictionaries that were compiled were bilingual. In these dictionaries, involving English and Shona, the bias was towards satisfying the needs of English-speaking users, as much of the detail, including the headword entries, was in English. However, with the need to empower the indigenous languages of the country, there was a deliberate move to promote Shona. This saw a change from the compilation of bilingual dictionaries to monolingual dictionaries which resulted in a different mode of diglossia as the dialects within Shona itself do not enjoy equal status in the dictionaries, because some dialects are given preference above others. This article traces the diglossic tendencies among languages and within the same language in dictionaries involving Shona. Keywords: DIGLOSSIA, LEXICOGRAPHY, SHONA, SOCIOLINGUISTICS, HIGH VARI-ETY, LOW VARIETY, SYNONYM, PHONOLOGY, ENTRY, TONE, DEFINITION Opsomming: Diglossiese beginsels in Sjonaleksikografie. Hierdie artikel beskou diglossie in Sjonawoordeboeke. Diglossie word hier gesien as die diskriminerende en begunstigende gebruik van ’n taal of ’n dialek in woordeboeke. Die hooftaal wat in Zimbabwe gepraat word, is Sjona. Oor ’n tydperk van ongeveer een en ’n half eeu, het ten minste twintig Sjona- leksikografiese publikasies verskyn, insluitende geglosseerde woordelyste en middelgroot woordeboeke, voorbeelde waarvan in hierdie artikel gebruik word om die diglossiese beginsels in Sjonaleksikografie te toon. Soos die geval is met baie tale, is Sjona ook in kontak met ander tale, onder hulle Engels wat gedurende die koloniale tydperk as die amptelike taal van die land verklaar is. Gevolglik was die woordeboeke wat saamgestel is, tweetalig. In hierdie woordeboeke waarby Engels en Sjona betrokke was, was die neiging om die behoeftes van Engelssprekende gebruikers te bevredig omdat baie van die besonderhede, insluitende die trefwoordinskrywings, in Engels was. Met die behoefte egter om die inheemse tale van die land te bemagtig, was daar ’n doelbewuste beweging om Sjona te bevorder. Dit het ’n verandering gebring weg van die samestelling van tweetalige woordeboeke na eentalige woordeboeke, wat gelei het tot ’n ander vorm van diglossie omdat die dialekte binne Sjona self nie gelyke status in die woordeboeke geniet nie, maar aan sommige voorkeur bo ander gegee word. Hierdie artikel spoor die diglossiese neigings na tussen tale en binne dieselfde taal in woordeboeke waarby Sjona betrokke is. Sleutelwoorde: DIGLOSSIE, LEKSIKOGRAFIE, SJONA, SOSIOLINGUISTIEK, HOÃ‹ VARIÃ‹TEIT, LAE VARIÃ‹TEIT, SINONIEM, FONOLOGIE, INSKRYWING, TOON, DEFINISIE